2021
DOI: 10.3390/ma14185137
|View full text |Cite
|
Sign up to set email alerts
|

Methylcellulose–Cellulose Nanocrystal Composites for Optomechanically Tunable Hydrogels and Fibers

Abstract: Chemical modification of cellulose offers routes for structurally and functionally diverse biopolymer derivatives for numerous industrial applications. Among cellulose derivatives, cellulose ethers have found extensive use, such as emulsifiers, in food industries and biotechnology. Methylcellulose, one of the simplest cellulose derivatives, has been utilized for biomedical, construction materials and cell culture applications. Its improved water solubility, thermoresponsive gelation, and the ability to act as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 144 publications
(316 reference statements)
1
18
0
Order By: Relevance
“…Application of all three coatings resulted in an increased thickness of the RP (Figure 2b). Although the MC film could not be seen on micrographs (Figure 1), the increase in grammage and thickness indicates that a film may have formed but remained invisible due to its high transparency [36].…”
Section: Resultsmentioning
confidence: 98%
“…Application of all three coatings resulted in an increased thickness of the RP (Figure 2b). Although the MC film could not be seen on micrographs (Figure 1), the increase in grammage and thickness indicates that a film may have formed but remained invisible due to its high transparency [36].…”
Section: Resultsmentioning
confidence: 98%
“…144,145 CNCs also provide mechanical reinforcement for optomechanically tunable functional gels. 146 The rod-like structures with negatively charged sulfate half-ester groups offer a route for the in situ synthesis of NCs. Hynninen et al demonstrated that glutathione-capped gold NCs can be prepared by interacting the metal precursor (HAuCl 4 ·3H 2 O) with CNCs.…”
Section: Patchy Ligand Distribution and Symmetry Breakingmentioning
confidence: 99%
“…26 MC and HPMC undergo temperature-responsive phase transitions through methoxy intermolecular hydrophobic interactions, and due to different numbers of methoxy substitutions, MC gels at 40-50 1C, leading to increased mechanical and scattering properties. 27 In contrast, HPMC cures at 75-90 1C. 28 In addition, the phase change temperature can be adjusted by physical or chemical modification of properties, such as NaCl, which reduces the LCST of MC to 32-34 1C.…”
Section: Temperature Sensitive Hydrogelsmentioning
confidence: 99%
“…When the number of methoxy substitutions in HPMC is reduced, the LCST can be lowered to 40 1C. 27 At this point, the LCST is close to the physiological temperature of the human body, which is conducive to in vivo studies. Although ethyl cellulose (EC) aqueous solution is thermosensitive, the viscosity decreases with increasing temperature, which is not conducive to the preparation of IVD in situ formed scaffolds.…”
Section: Temperature Sensitive Hydrogelsmentioning
confidence: 99%